Nitrogen Production by Efficiently Removing Oxygen From Air Using a Perovskite Hollow-Fiber Membrane With Porous Catalytic Layer - Hu, Tianmiao; Zhou, Hangyue; Peng, Hui; Jiang, Heqing (Frontiers in Chemistry, 2018)
Nowadays, nitrogen is mainly produced from air by cryogenic distillation, pressure-swing adsorption (PSA) and polymeric membrane technology. In this paper, we report a perovskite membrane-based nitrogen production route, which is basically driven by methane combustion. By coupling air separation with methane combustion on the opposite sides of oxygen-permeable perovskite membrane, most of oxygen in air is efficiently removed through the perovskite membrane and then consumed by methane oxidation. The production of nitrogen with purity of 98%-99% was successfully achieved, and remained stable over 120 h, with a methane conversion of 71%-73% on the other side of perovskite membrane. This work demonstrates that the joint use of oxygen-permeable perovskite membrane and methane oxidation is a promising strategy for nitrogen production and inspires more research efforts in the field of gas separation.